The co-management of HIV and chronic non-communicable diseases in the Dominican Republic: A qualitative study. - Deshira D Wallace; Amarilis Then-Paulino; Gipsy Jiménez Paulino; Flabia Tejada Castro; Stephanie Daniela Castro; Kartika Palar; Kathryn P Derose (PLoS ONE, 2023)
People living with HIV and a non-communicable disease (NCD) experience multi-level barriers when co-managing multiple conditions. We explored the factors affecting living with multiple chronic conditions in the Dominican Republic. We conducted 21 in-depth interviews from October 2019-February 2020 with Dominican adults who participated in a food security intervention and managed HIV and at least one chronic NCD. Using thematic analysis, we explored participant lived experiences co-managing multiple chronic conditions. All participants (mean age = 45.5 years) were linked to HIV care, but only three were linked to NCD-specific care. Individual-level barriers to managing NCDs included limited education and limited self-efficacy for self-management. Interpersonally, barriers included limited rapport building with an NCD-specific specialist. Structural barriers to managing NCDs were no health insurance, poor referral systems, and limited financial assistance. Health system adaptation requires equitably considering the needs of individuals managing multiple chronic conditions. Key factors to address include patient-provider relationships, improved referral systems, accessibility and availability of specialists, and financial assistance.